Fundamentals of advanced accounting - Hoyle, Joe Ben; Doupnik, Timothy S.; Schaefer, Thomas F. (McGraw-Hill Irwin, 2011)
Fundamentals of Advanced Accounting, 4th edition is ideal for those schools wanting to cover 12 chapters in their advanced accounting course. This brief yet concise text allows students to think critically about accounting, just as they will do preparing for the CPA exam. With this text, students gain a well-balanced appreciation of the Accounting profession. The 4th edition introduces the students to the fields many aspects, while focusing on past and present resolutions. The text continues to show the development of financial reporting as a product of intense and considered debate that continues today and into the future as it originates from Hoyles big text Advanced Accounting